ANALISIS KINERJA KEUANGAN PADA PEMERINTAH DESA DI KECAMATAN PINO RAYA DAN KECAMATAN BUNGA MAS KABUPATEN BENGKULU SELATAN DI MASA PANDEMI COVID-19 - Amira Nabila; Fadli, Fadli; Tiolina Evi Nausta pardede (Bajang Institute, 2025)
This research aims to analyze and describe the financial performance of village governments in Pino Raya and Bunga Mas Districts, South Bengkulu Regency, during the Covid-19 pandemic period (2020–2021). The study employed a purposive sampling technique, with a sample consisting of 30 villages that submitted their APBDes (Village Budget Realization Reports) to the Office of Village Community Empowerment in South Bengkulu. The data used in this research included both secondary data in the form of budget realization reports and primary data obtained through observation. The analytical methods applied were descriptive statistical analysis and observational techniques. The evaluation of financial performance was conducted using the value for money approach, which assesses performance based on three key indicators: economy, efficiency, and effectiveness. The findings of the study indicate that, on average, the financial performance of the village governments was categorized as economical, relatively ineffective in terms of efficiency, and moderately effective in achieving the planned budget targets. These results suggest that although financial management was prudent during the pandemic, improvements are still needed, particularly in enhancing the efficiency of spending to optimize local revenue potential.